Pengembangan Video Tutorial Sebagai Media Pembelajaran Analisis Regresi Pada Perkuliahan Ekonometrika - Ihsan, Ihsan; Yaqutunnafis, Lale; Salkiah, Baiq (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This development research uses a 4D model approach which is divided into four development stages; Define, Design, Develop, Disseminate. The aim is to produce two video tutorials that are valid and suitable as a source and learning medium for regression analysis in econometrics lectures. Media validation was carried out by 3 experts and product trials were carried out on 23 6th semester students who were taking econometrics courses at the Program Study Economic Education at Nahdlatul Wathan Mataram University, TA. 2022/2023. The results of the research show that video tutorials are very suitable as a source and learning medium for regression analysis which is confirmed based on the total average expert validation results of 3.73 with a percentage of 93.35% and 100% having a meaningful value which is strengthened based on students' positive responses during the trial. product, where students are very satisfied and enjoy attending lectures, obstacles and difficulties in regression analysis can be minimized. Apart from that, other findings in the field also show that the development of video tutorials can change students' negative perspectives in econometrics courses because the complexity of the material can be simplified, making it easier to master the material and improving software-based analysis skills.